Contracted Foal Syndrome Associated with Multiple Malformations in Two Foals. (14th February 2013) - Binanti, D.; Zani, D. D.; De, D.; Turci, T.; Zavaglia, G.; Riccaboni, P.
Summary Congenital anomalies in horses are very rare, and contracted foal syndrome is one of the most commonly reported. This malformation is characterized by contraction of the joints of the forelimbs and/or hindlimbs. In addition, the syndrome can be characterized by vertebral column malformations, such as scoliosis or torticollis, and cranial deformity. The present report describes the radiological and necroscopical findings of multiple rare malformations in two foals. Both foals showed skeletal abnormalities and fenestration of the abdominal cavity. Other pathological findings include a interventricular septal defect in one and a unilateral hydronephrosis and partial hydroureter in the other foal. Although in this report a specific aetiology could not be provided, insecticides treatment provided during the second month of pregnancy might play a role in the pathogenesis of these malformations.